2002
DOI: 10.1073/pnas.132274599
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the amino-terminal domain of syntaxin 6, a SNAP-25 C homolog

Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins are required for intracellular membrane fusion, and are differentially localized throughout the cell. SNAREs on vesicle and target membranes contain ''SNARE motifs'' which interact to form a four-helix bundle that contributes to the fusion of two membranes. SNARE motif sequences fall into four classes, homologous to the neuronal proteins syntaxin 1a, VAMP 2, and the N-and C-terminal SNARE motifs of SNAP-25 (S25N and S25C), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Similarly, all Qa-SNAREs exhibit a very similar domain architecture, carrying an N-terminal three-helix bundle structure (Fernandez et al, 1998;Lerman et al, 2000;Misura et al, 2000;Munson et al, 2000;Dulubova et al, 2001). Interestingly, several of the Qb-and the Qc-SNAREs possess an N-terminal three-helix bundle as well (Antonin et al, 2002a;Misura et al, 2002;Fridmann-Sirkis et al, 2006). This hints at a common origin of all three main Q-SNARE groups from a prototypic Q-SNARE.…”
Section: Evolution Of the Snare Apparatus Is Linked To The Developmenmentioning
confidence: 96%
“…Similarly, all Qa-SNAREs exhibit a very similar domain architecture, carrying an N-terminal three-helix bundle structure (Fernandez et al, 1998;Lerman et al, 2000;Misura et al, 2000;Munson et al, 2000;Dulubova et al, 2001). Interestingly, several of the Qb-and the Qc-SNAREs possess an N-terminal three-helix bundle as well (Antonin et al, 2002a;Misura et al, 2002;Fridmann-Sirkis et al, 2006). This hints at a common origin of all three main Q-SNARE groups from a prototypic Q-SNARE.…”
Section: Evolution Of the Snare Apparatus Is Linked To The Developmenmentioning
confidence: 96%
“…The N-terminal domains of Tlg2p, Vti1p, and the Tlg1p homolog syntaxin 6 have recently been shown to all possess a strong structural similarity to that of syntaxin, but none appears to form a closed conformation in vitro (Antonin et al, 2002;Dulubova et al, 2002;Misura et al, 2002). It may be that intramolecular SNARE interactions are not always readily detected in vitro, because the results of the liposome fusion work are most consistent with the model that an unidentified factor catalyzes SNARE assembly by displacing an inhibitory domain.…”
Section: Vps51 Is Required For the Binding Of Garp To The Tgn T-snarementioning
confidence: 99%
“…Recent studies have demonstrated that many nonsyntaxin SNAREs, including the Tlg1p homolog syntaxin 6, have a conserved, independently folded N-terminal domain that is structurally similar to that of syntaxin (Dulubova et al, 2001;Tochio et al, 2001;Misura et al, 2002). To identify which domain of Tlg1p is responsible for binding Vps51p, we expressed the entire soluble (cytosolic) por- Figure 5.…”
Section: Vps51p Is Required For the Binding Of Vps52/53/54 To The N-tmentioning
confidence: 99%
“…For example, caveolar endocytosis was dramatically reduced following inhibition of Stx6; however, this was not due to the direct participation of the SNARE to the process but upon the block of membrane microdomain delivery to the plasmalemma (Choudhury et al, 2006). Moreover, the SNARE motif of Stx6 appears structurally and functionally more homologous to the Qc motif of the SNAPs than to the Qa motif of other syntaxins (Bock et al, 2001;Misura et al, 2002). Therefore, a SNARE complex including both Stx6 and SNAP23 might be unlikely because it would be composed, together with the Qb motif of SNAP23 and the R motif of VAMP4, by two Qc and no Qa motifs.…”
Section: Journal Of Cell Science 121 (18)mentioning
confidence: 99%